Reliability Improvement of the Smart Distribution Grid Incorporating EVs and BESS via Optimal Charging and Discharging Process Scheduling - Jozi, Fatemeh; Abdali, Ali; Mazlumi, Kazem; Hosseini, Seyed Hadi (Frontiers in Energy Research, 2022)
The use of large-scale electric vehicles (EVs), along with technological advances in battery energy storage systems (BESS), offers numerous technical and economic benefits to the smart distribution system. Parking lots not only provide EV owners with the opportunity to charge their BESS but also contribute power to the grid via vehicle to grid (V2G) technology, which significantly improves the reliability of distribution systems. In addition, parking lots equipped with V2G capability are able to participate in the electricity market as a producer. In this paper, the reliability of a smart radial distribution system in the presence of EVs is investigated. It should always be borne in mind that parking lots can improve system reliability if the charging and discharging strategies are optimally and correctly scheduled. On the other hand, the parking lot participates in sending power to the grid in a situation where the profit is appropriate. Accordingly in this paper, first, five optimal strategies for scheduling the process of EV charging and discharging in a parking lot equipped with V2G capability are proposed, with the aim of maximizing parking profits. The proposed strategies include constraints on the amount of power exchange between the parking lot and the distribution system, as well as the random and stochastic nature of quantities such as when EVs enter and exit the parking lot and their BESS charge amounts when entering the parking lot. The results demonstrate that using the proposed optimal charging and discharging strategies scheduling increases the parking profit by 31% and also improves the reliability of the understudy distribution system by 9%.